Anti-inflammatory and anti-pyretic properties of spirulina platensis and spirulina lonar: a comparative study - Somchit, Muhammad Nazrul; Mohamed, Nor Azura; Ahmad, Zuraini; Zakaria, Zainul Amiruddin; Shamsuddin, Lokman; Omar Fauzee, Mohd Sofian; Abdul Kadir, Arifah (University of Karachi, 2014)
Spirulina spp. is a blue-green algae belongs to the family of Oscillatoriaceae, which having diverse biological activity. The aim of this current study was to evaluate and compare the anti-pyretic and anti-inflammatory activity of Spirulina platensis/SP and Spirulina lonar/SL extracts. In the anti-pyretic study, the ability to reduce the rectal temperature of rats induced pyrexia with 2g/kg Brewer’s Yeast (BY) was performed. Rats were dosed either 2 or 4 mg/kg SP or SL. Rectal temperature was taken every hour for 8 hours. Results shown that there were significant dosedependent (p<0.05) reduction of both treatments. However, SP treatment revealed faster reduction in rectal temperature. For anti inflammatory activity, the reduction in the volume of paw edema induced by Prostaglandin E2 (100 IU/rat intraplantar) was measured. Rats were dosed orally with 2 or 4 mg/kg SP or SL. The paw edema was measured every 30 minutes for 4 hours using plethysmometer. Results had shown a significant dose dependent reduction in diameter of paw edema (p<0.05). The finding suggests that SP and SL extracts have anti-pyretic and anti inflammatory properties. However, SP was found to be more effective than SL as anti-pyretic and anti-inflammatory agent.